Potential Adverse Effects Caused by Gamification Elements in mHealth Apps - Rocha, Ivan; Silveira, Milene Selbach (Journal of the Brazilian Computer Society, 2024)
Health practices using mobile devices (known as mobile health, or mHealth) have increased in recent years. To increase users’ motivation to use it, mHealth researchers and developers have started to use gamification. However, no studies were found on the negative aspects of gamification in health. This work aims to determine the potential adverse effects of gamification in mHealth applications and analyze how different types of gamification elements can cause these effects. To this end, an analysis of 70 gamified mHealth applications extracted from the Google Play Store was performed to identify which gamification elements are commonly applied in mHealth. Then, to identify the negative aspects of gamification in mHealth and how the gamification elements can be related to them, a systematic review of the literature was carried out, where 37 studies were selected. Finally, a study was carried out with users of gamified mHealth applications to analyze in practice what was found in the previous steps. The results of these studies show which gamification elements are the most used in mHealth applications, the potential adverse effects found, and a list of which gamification elements can cause these effects. The results of this study provide insights into the risks associated with gamification in mHealth applications and can make developers, designers and professionals aware of these harmful issues.